2017
DOI: 10.3390/inorganics5030044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro (Anticancer) Evaluation of η6-Arene Ruthenium Complexes Bearing Stannyl Ligands

Abstract: Treatment of the known half-sandwich complexes of the type [(η 6-C 6 H 6)RuCl 2 (P(OR) 3)] (R = Me or Ph) with SnCl 2 yielded three new half-sandwich ruthenium complexes (C1-C3): [(η 6-C 6 H 6)RuCl(SnCl 3)(P(OMe) 3)] (C1), [(η 6-C 6 H 6)RuCl(SnCl 3)(P(OPh) 3)] (C2) and the bis-stannyl complex [(η 6-C 6 H 6)Ru(SnCl 3) 2 (P(OMe) 3)] (C3) by facile insertion of SnCl 2 into the Ru-Cl bonds. Treatment of the known complexes [(η 6-C 6 H 6)RuCl(SnCl 3)(PPh 3)] and [(η 6-C 6 H 6)RuCl 2 (PPh 3)] with 4-dimethylaminopyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…One of the causes that leads to low toxicity of these compounds is the lack of lipophilic groups, decreasing the cellular uptake of these complexes. 33,51,52 To investigate the effects on cell morphology of the most selective compound, complex 1 was incubated with the MDA-MB-231 cells at different concentrations ( Figure S23 of SI section) proportional to the IC 50 values. Negative control cells have a spindle-shaped phenotype in both strains, while cells treated with complex 1, especially at 24 μM for MDA-MB-231 (2 × IC 50 , 24 h), have spherically shaped cells (which may be indicative of apoptosis), 33,[53][54][55][56][57] in addition to damaged cell bodies, ongoing cell death, loss of adhesion and confluence.…”
Section: Biological Anticancer Experimentsmentioning
confidence: 99%
“…One of the causes that leads to low toxicity of these compounds is the lack of lipophilic groups, decreasing the cellular uptake of these complexes. 33,51,52 To investigate the effects on cell morphology of the most selective compound, complex 1 was incubated with the MDA-MB-231 cells at different concentrations ( Figure S23 of SI section) proportional to the IC 50 values. Negative control cells have a spindle-shaped phenotype in both strains, while cells treated with complex 1, especially at 24 μM for MDA-MB-231 (2 × IC 50 , 24 h), have spherically shaped cells (which may be indicative of apoptosis), 33,[53][54][55][56][57] in addition to damaged cell bodies, ongoing cell death, loss of adhesion and confluence.…”
Section: Biological Anticancer Experimentsmentioning
confidence: 99%
“…The anticancer or biological activity investigations of any of these four classes of compounds or elucidations of their bonding nature by theoretical methods have not previously been evaluated. Moreover, given our previous numerous studies on ruthenium arene stannyl and stannate complexes, as well as their germanium analogues, ,, the extension to osmium is expected to yield different biological activities given the rather inert nature of Os­(II) vs Ru­(II) (see above). This hence motivated us to explore the analogous osmium chemistry with a view of biological anticancer applications, not as a mere extension from Ru, but expecting different in vitro biological activities compared to analogous ruthenium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported a series of neutral ruthenium-based germyl ([Ru]−GeCl 3 ) and stannyl ([Ru]−SnCl 3 ) complexes that displayed less than optimal cytotoxic activity on numerous cell lines in vitro (Scheme 1). 13,15 In contrast, ruthenium germanate and stannate salt complexes displayed potent and promising cytotoxic activity on two breast cancer cell lines (MCF-7 and MDA-MB-231) and good selectivity, suggesting that the ionic nature of the complexes influences their biological effects. 14 Osmium, as a heavier analogue of ruthenium, might be expected to be a suitable metal for anticancer applications; however, when compared to ruthenium, research into osmiumbased anticancer agents is less pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…Goitia and co-workers have reported that gold­(I)/complex with 2-thiouracil exhibits excellent cytotoxic activity against PC-12 and NIH-3T3 cell lines . Thus, having in mind that Ru­(II) complexes have been investigate in the development of compounds with anticancer properties, to evaluate the structural modification on biological properties of ruthenium complexes with 2-thiouracil derivatives, we present here the synthesis of two new monocationic complexes, expecting that they will have good cytotoxicity against cancer cells. …”
Section: Introductionmentioning
confidence: 99%